Tandem catalysts for the selective hydrogenation of butadiene with hydrogen generated from the decomposition of formic acid. Issue 53 (19th May 2021) - Carrales-Alvarado, D. H.; Dongil, A. B.; Guerrero-Ruiz, A.; Rodríguez-Ramos, I.
Abstract : We report for the first time the selective hydrogenation of 1, 3-butadiene to butene using formic acid as the hydrogen source with 1 wt% Pd/carbon in a continuous flow reactor. Abstract : We report for the first time the selective hydrogenation of 1, 3-butadiene to butene using formic acid as the hydrogen source with 1 wt% Pd/carbon in a continuous flow reactor. The catalytic results show that the selectivity is even higher when formic acid is used compared to gas hydrogen.